A Randomized Placebo-Controlled Trial of Low- Versus Moderate-Dose Vitamin D3 Supplementation on Bone Mineral Density in Postmenopausal Women With HIV. (1st March 2019) - Yin, Michael T.; RoyChoudhury, Arindam; Bucovsky, Mariana; Colon, Ivelisse; Ferris, David C; Olender, Susan; Agarwal, Sanchita; Sharma, Anjali; Zeana, Cosmina; Zingman, Barry; Shane, Elizabeth
Abstract : Background: Prevalence of osteoporosis and fracture is increased among older people with HIV. We compared the effects of low (1000 IU) vs moderate (3000 IU) vitamin D3 (VitD) supplementation on areal bone mineral density (aBMD) and volumetric bone mineral density (vBMD) in African American and Hispanic postmenopausal women with HIV on antiretroviral therapy. Methods: We performed a 12-month prospective, randomized, double-blind, placebo-controlled study with primary outcomes of change in aBMD by dual-energy X-ray absorptiometry (DXA) and secondary outcomes of change in vBMD by quantitative computed tomography and bone turnover markers. An intent-to-treat analysis was performed on 85 randomized subjects (43 low and 42 moderate) for primary DXA outcomes, and complete case analysis was performed for secondary outcomes. Results: Mean age was 56 ± 5 years, median CD4 count was 722 cells/mm 3, and 74% had HIV RNA ⩽ 50 copies/mL. Serum 25-OHD was higher in the moderate than low VitD group at 6 months (33.1 ± 10.3 vs 27.8 ± 8.1 ng/mL, P = 0.03) and 12 months, but parathyroid hormone levels remained similar. Percent change in aBMD, vBMD, and bone turnover markers did not differ between low and moderate VitD groups before or after adjustment for baseline aBMD. Conclusions: VitD supplementation at 3000 IU daily increased mean total 25-OHD levels in postmenopausal women with HIV, but we did not find evidence of an effect on BMD beyond those observed with 1000 IU daily. Future studies are necessary to determine whether VitD supplementation is beneficial in this patient population, and if so, what dose is optimal for skeletal health.